1993
DOI: 10.1159/000175870
|View full text |Cite
|
Sign up to set email alerts
|

Effects of a Preload Increase on Ventricular Filling in Coronary Artery Disease

Abstract: This study was conducted to investigate the effects of a preload increase on ventricular filling dynamics in 50 coronary artery disease patients both before and immediately after leg elevation. Mitral and tricuspid peak E and A velocities and the mitral E/A velocity ratio increased after leg elevation whereas isovolumic relaxation time and mitral deceleration time decreased. The increase in tricuspid peak A velocity after leg elevation was related to the positivity of the exercise stress test (p = 0.01). The i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
1
3

Year Published

1999
1999
2007
2007

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(9 citation statements)
references
References 13 publications
(19 reference statements)
0
5
1
3
Order By: Relevance
“…This result may explain that the prognostic value of the index is maintained despite changes in preload 27 . Previous studies have reported an increase in preload to increase ICT and ET but reduce IRT 28,29 . In contrast, our findings are incompatible with these findings in patients with MS, which is a disease causing preload reduction.…”
Section: Discussioncontrasting
confidence: 88%
“…This result may explain that the prognostic value of the index is maintained despite changes in preload 27 . Previous studies have reported an increase in preload to increase ICT and ET but reduce IRT 28,29 . In contrast, our findings are incompatible with these findings in patients with MS, which is a disease causing preload reduction.…”
Section: Discussioncontrasting
confidence: 88%
“…Duration difference between the atrial reversal flow in the pulmonary vein and mitral A wave by pulse wave Doppler echocardiography was correlated with LV end diastolic pressure [10,11,12,13,14,15,16,17,18,19,20]. Tissue Doppler echocardiography (TDE) was found to be a new method to evaluate LV systolic and diastolic dysfunction [21].…”
Section: Introductionmentioning
confidence: 99%
“…The restrictive filling pattern is defined as an increase in early diastolic E wave filling velocity, an E/A ratio >2 and a decrease in deceleration time (<150 ms) 1 . Both pulse wave Doppler echocardiography (PW) and color Doppler echocardiography are known to be preload‐dependent 2–12 . Pulse wave Doppler echocardiographic tracing is influenced by preload status.…”
mentioning
confidence: 99%
“…Pulse wave Doppler echocardiographic tracing is influenced by preload status. The decrement of preload status is associated with decrement in peak early diastolic filling velocity into the left ventricle (LV) 2–12 . Because a shift between restrictive pattern and abnormal relaxation pattern can be accomplished by Valsalva maneuver and modified preload status, 13–16 differentiating between the normal and pseudonormal pattern can be confusing.…”
mentioning
confidence: 99%
See 1 more Smart Citation